PENGARUH SHIFT KERJA TERHADAP STRESS KERJA PADA PERAWAT DI RUANG RAWAT INAP DI RUMAH SAKIT BHAKTI TIMAH PANGKALPINANG - Fajrianti, Gita (JURNAL SMART ANKES, 2020)
Shift work or shift work is the application of a work system with a 24-hour rotation that requires work shifts. Shift work can affect stress, stress can be described as a force that is internalized to urge or grip and arise in a person as a result of difficulty in adjusting. Work stress that has an impact on decreased work performance, health and emotional problems and many impacts that can be caused by work stress. In the initial study there were 11 nurses who worked shifts in the inpatient room who said they experienced work stress. This study aims to analyze the effect of work shifts on work stress on nurses in the inpatient room at Bhakti Timah Pangkalpinang Hospital in 2019. The research method used in this research is descriptive exploratory. This study used a qualitative approach while the informants of this study included 7 nurses who worked shifts in the inpatient room and 2 heads of inpatient rooms at the Bhakti Timah Hospital Pangkalpinang. The research instrument used interview guidelines, image recording devices, and voice recording devices. This research concludes that there is still work stress experienced by nurses who work shifts in the inpatient room at the Bhakti Timah Pangkalpinang Hospital as seen from the effects such as health problems and emotional instability. It is recommended to increase the number of nurses who work shifts in inpatient rooms and provide regular health check services (in the K3 promotion program) for nurses so as to minimize fatigue and health problems.